The feasibility and usability of a personal health record for patients with multiple sclerosis: a 2-year evaluation study - van den Berg, Liselot N.; Aardoom, Jiska J.; Kiveron, Léone E.; Botterweg, Robert D.; van den Akker – van Marle, M. Elske; Chavannes, Niels H.; Hoitsma, Elske (Frontiers in Human Neuroscience, 2024)
Multiple sclerosis (MS) is a persistent inflammatory condition impacting the brain and spinal cord, affecting globally approximately 2.8 million individuals. Effective self-management plays a crucial role in the treatment of chronic diseases, including MS, significantly influencing health outcomes. A personal health record (PHR) is a promising tool to support self-management, potentially empowering patients and enhancing their engagement in treatment and health. Despite these promising aspects, challenges in implementation persist. This study aimed to assess the feasibility and usability of the PHR. Secondary objectives included evaluating implementation determinants, and exploring preliminary effects on quality of care for both patients and healthcare professionals (HCPs), self-management, self-efficacy for patients, job satisfaction, efficiency, and demand for HCPs, and preliminary effects on costs and health-related quality of life. This study had a mixed-methods design. Quantitative data of patients (n=80) and HCPs (n=12) were collected via self-reported questionnaires at baseline (T0), after one year (T1), and after two years (T2). One focus group interview was conducted at T2 with patients (n=7), and another one with HCPs (n=4), to get a more in-depth understanding of the objectives. Most patients never logged in during the first year and logged in a couple of times per year during the second year, averaging around 15 minutes per log-in session. The HCPs mainly logged in a couple of times per year over the two years with an average use of six minutes per session. Patient and HCP usability and satisfaction scores were moderate. Multiple facilitators and barriers were identified by both patients and HCPs, such as (in)sufficient knowledge of how to use the PHR, lack of staff capacity and ICT obstacles. No significant differences were found in the preliminary effects. Qualitative data showed that both patients and HCPs saw the benefit of the PHR in terms of gaining more insight into disease progression, but challenges remained, such as log-in issues and information retrieval difficulties. The evolving nature of PHRs requires ongoing evaluation and adaptation to optimize their potential benefits. Utilizing a participatory design approach and a dedicated implementation team could help in achieving this optimization, ultimately enhancing their adoption.